Another Piece of the Puzzle of Anomalous Connectivity in Joubert's Syndrome - Meoded, Avner; Kukreja, Marcia; Orman, Gunes; Boltshauser, Eugen; Huisman, Thierry A.G.M. (Neuropediatrics, 2021)
We report on the conventional and diffusion tensor imaging (DTI) findings of a 2-year-old child with clinical presentation of Joubert's Syndrome (JS) and brainstem structural abnormalities as depicted by neuroimaging.Conventional magnetic resonance imaging (MRI) showed a “molar tooth” configuration of the brainstem. A band-like formation coursing in an apparent axial plane anterior to the interpeduncular fossa was noted and appeared to partially cover the interpeduncular fossa.DTI maps and three-dimensional (3D) tractography demonstrated a prominent red-encoded white matter bundle anterior to the midbrain. Probable aberrant course of the bilateral corticospinal tracts (CST) was also depicted. Absence of the decussation of the superior cerebellar peduncles and elongated thickened, horizontal superior cerebellar peduncle (SCP) reflecting the molar tooth sign were also shown.Our report and the review of the published cases suggest that DTI and tractography may be very helpful to differentiate between interpeduncular heterotopias and similarly located white matter bundles corroborating the underlying etiology of axonal guidance disorders in the complex group of ciliopathies including JS. Our case represents an important additional puzzle piece to explore the variability of these ciliopathies.
Keywords: Joubert's syndrome; interpeduncular mass; diffusion tensor imaging; tractography; ciliopathy